2002
DOI: 10.1191/1358863x02vm423oa
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent pneumatic compression for the treatment of lower extremity arterial disease: a systematic review

Abstract: This study aimed to identify the role of intermittent pneumatic compression in treating peripheral arterial disease and to investigate the types of treatment programs that are most effective. Data was sourced from English-language articles which were identi ed by a computer search using MEDLINE from 1966 to 2001, followed by extensive bibliography review. Studies were included if they contained pertinent material involving a compression device and arterial ow dynamics in lower limbs. A total of 26 English-lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 29 publications
0
22
0
3
Order By: Relevance
“…These treatment parameters were selected according to prior studies in which the impact of IMC on popliteal arteral flow was optimized. 7 The device also includes integrated software that records the duration of use for each day and allows monitoring of the degree of compliance with the prescribed two hour/day, seven days/week, three-month treatment prescription. In order to assess compliance in an unbiased way, the patients were not informed of the existence of this software during the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These treatment parameters were selected according to prior studies in which the impact of IMC on popliteal arteral flow was optimized. 7 The device also includes integrated software that records the duration of use for each day and allows monitoring of the degree of compliance with the prescribed two hour/day, seven days/week, three-month treatment prescription. In order to assess compliance in an unbiased way, the patients were not informed of the existence of this software during the study.…”
Section: Methodsmentioning
confidence: 99%
“…6 Prior studies have also demonstrated that IPC increases lower limb arterial flow and could therefore be useful in patients with PAD. 7 Indeed, therapeutic effects have been identified in studies showing a 3.2 Ϯ 1.6-fold increase in resting popliteal artery blood flow in patients with claudication in response to IPC applied to the calf 8 and isotope studies showing an increase in calf muslce perfusion with IPC applied to the foot. 9 Although promising, the use of IPC devices for claudication has not been pursued extensively because of certain limitations.…”
mentioning
confidence: 97%
“…In recent years, evidence has been provided showing that this strategy is an efficacious therapeutic option for patients with peripheral artery disease (PAD) (11,13,24). In a randomized controlled trial, Delis and Nicolaides (13) showed that a minimum of 2.5 h of daily IPC application for 5 mo improves walking distance, ankle brachial index, and quality of life in stable claudicants.…”
mentioning
confidence: 99%
“…Claudication distance, rest pain, and rates of limb salvage were improved across the spectrum of trials performed, associated with increased arterial blood flow, peak systolic velocity, end diastolic velocity and pulse volume. 48 A small randomized study with 12 months follow-up (n=30) in patients with stable intermittent claudication concluded that walking distance improved in these patients. 49 In addition to improved walking distance in stable claudicants, a prospective randomised controlled study with 1 year follow-up found an improvement in the ankle brachial pressure index, which is a measurement of peripheral haemodynamics, and improvement in quality of life.…”
mentioning
confidence: 99%